Perancangan Ulang dan Analisa Mesin Benchtop Injection Molding dengan Metode VDI 2222 - Adhiharto, Riky; Nusantoro, Adel Bangun; Komara, Asep Indra; Wigenaputra, Dadan Heryada (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Injection molding is a process by which plastic is heated until it softens to fill a closed mold and form a product. One of them is the benchtop injection molder, where the machine that was previously made at POLMAN had problems, namely the main frame structure and injection mechanism which was less sturdy during the injection process and the heating system which overheated. Based on these problems, a redesign and analysis was carried out on the existing benchtop injection molder machine. The design methodology used is VDI 2222, which is a technical concept design methodology suitable for product development. Heat Transfer Simulation on existing and latest designs using COMSOL Software with geometry, material, temperature, fluid inlet and outlet, and mesh parameters. The results obtained were uneven heat distribution to the middle of the existing barrel at a temperature of 4600K, while the new barrel had an even heat distribution to the middle at 4730K at the 10th second. The latest machine weighs 17.78 kg, dimensions 775 x 266 x 426 mm, barrel capacity 19 grams with an aluminum frame and tight band heater installation.